Impostor Phenomenon and L2 willingness to communicate: Testing communication anxiety and perceived L2 competence as mediators - Brauer, Kay; Barabadi, Elyas; Aghaee, Elham; Alrabai, Fakieh; Elahi Shirvan, Majid; Sendatzki, Rebekka; Vierow, Linnea Marie (Frontiers in Psychology, 2023)
The Impostor Phenomenon (IP) describes experiences of perceived intellectual fraudulence despite the existence of objectively good performances, and it is a robust predictor of experiences and outcomes in higher education. We examined the role of the IP in the domain of second language (L2) acquisition by testing its relations with a robust predictor of L2 use, willingness to communicate (WTC). We collected self-reports of 400 adult Iranian L2 learners and tested the associations between the IP and WTC. As expected, we found a negative association between IP and WTC (r = -.13). When testing a mediation model with perceived competence and communication anxiety as parallel mediators, we found evidence for full mediation via perceived competence. Our findings show the importance of considering self-evaluations in the domain of L2 acquisition. Further implications and limitations are discussed.